The importance of testing Smart Grid IEDs against security vulnerabilities - Weerathunga, Pubudu Eroshan; Cioraca, Anca (Annual Conference for Protective Relay Engineers : [proceedings], 2016)
As the Smart Grid becomes highly interconnected, the power protection, control, and monitoring functions of the grid are increasingly relying on the communications infrastructure, which has seen rapid growth. At the same time concerns regarding cyber threats have attracted significant attention towards the security of power systems. A properly designed security attack against the power grid can cause catastrophic damages to equipment and create large scale power outages. The smart grid consists of critical IEDs, which are considered high priority targets for malicious security attacks. For this reason it is very important to design the IEDs from the beginning with cyber security in mind, starting with the selection of hardware and operating systems, so that all facets of security are addressed and the product is robust and can stand attacks. Fact is that the subject of cyber security is vast and it covers many aspects. This paper focuses mainly on one of these aspects, namely the aspect of IED firmware system testing from the security point of view. The paper discusses practical aspects of IED security testing, and introduces the reader to types of vulnerability exploitations on the IED communication stack and SCADA applications, practical aspects of security testing, the importance of early vulnerability detection and ways in which the security testing helps towards regulatory standards compliance, such as NERC-CIP. Finally, based on the results from the simulated attacks, the paper discusses the importance of good security practices in design and coding, so that the potential to introduce vulnerabilities is kept to a minimum. Designing with security in mind also includes good security practices, both in design and coding, and adequate policies for the software development process. Critical software development milestones must be established, such as design and test documentation review, code review, unit, integration and system testing.